Novel two-dimensional "ring and chain" morphologies in Langmuir-Blodgett monolayers of PS-b-PEO block copolymers effect of spreading solution concentration on self-assembly at the air-water interface - Cheyne, Robert B (Langmuir : the ACS journal of surfaces and colloids, 2005)
A polystyrene-b-poly(ethylene oxide) (PS-b-PEO) (MW = 141k, 11.4 wt% PEO) diblock copolymer in the hydrophobic regime was spread from chloroform solutions of various concentrations at the air-water interface, and the resultant monolayers were transferred to glass substrates and imaged using atomic force microscopy. Monolayers prepared under identical conditions were also characterized at the air-water interface via Langmuir compression isotherms. The effects of spreading solution concentration on surface features, compressibility, and limiting mean molecular area were determined, revealing several interesting trends that have not been reported for other systems of PS-b-PEO. Spreading solutions > or = 0.50 mg/mL resulted almost exclusively in dot and spaghetti morphologies, with no observed continent features, which have been commonly found in more hydrophobic systems. For lower spreading solutions, < or = 0.25 mg/mL, we observed a large predominance of two novel surface morphologies, nanoscale rings and chains. The surface pressure (pi)-area (A) isotherms also exhibited a unique dependence on the spreading solution concentration, with limiting mean molecular areas and isothermal compressibilities of PS-b-PEO monolayers increasing below a critical concentration of spreading solution, suggesting a greater contribution from the PEO blocks. These results suggest that PS chain entanglement prior to solvent evaporation plays an important kinetic role in the extent of PEO adsorption at the air-water interface and in the morphologies of the resulting self-assembled surface aggregates